A curta duração do ciclo da cultura aumenta a limitação de nitrogênio da soja de alta produtividade - Munareto, Guilherme Guerin (2021)
Soybean productivity has doubled in the last two decades, driven by genetic improvement (earlier cultivars) and management practices. Published studies indicate limited nitrogen (N-gap) for high-yield soybeans, that is, as soil nitrogen sources (NS) in conjunction with N2 biological fixation (NBF) are not sufficient to require the crop's N demand. We hypothesize that a shorter crop cycle duration leads to a larger N-gap. To test, we followed a protocol based on the N demand of the crop according to its potential, synchronizing the nutrient supply with the N demand and the crop phenology, performing fractional N applications (treatment, N-complete) in relation to a zero-N treatment that forced a culture dependent on FBN and NS. Experiments were carried out in five locations in southern Brazil, with a dataset with large potential yield PP 2.7 to 7.0 Mg ha-¹, maturation group (GM) 5.0 to 6.8 and duration of cycle (102 to 138 days). Aboveground dry mass (MSS) was collected throughout the cycle to evaluate the crop growth rate (TC) of the two N treatments. Grain, protein and oil yield and their concentrations, grain mass, number of grain and legumes were measured in both N treatments at physiological maturity. The data set separated into three groups: short (GM, 5.0 to 5.2); medium (GM, 5.5 to 5.9) and long (GM, 6.2 to 6.8), henceforth called. The results indicate that the shorter the cycle, the greater the N-gap in grain yield, short GM with N-gap (18.5%, 0.85 Mg ha-¹), medium GM (3.5%, 0, 15 Mg ha-¹) and GM long N-gap close to zero contrasting the N-complete minus the zero-N. The shorter MG had the highest response to N addition, increasing a maximum TC (3 gm−² d-¹), MSS in R3 (1.1 Mg ha-¹), grain mass (16 mg) number of legumes and grains (14.4% and 13.5%, respectively). Protein productivity also increased (short GM, 0.34 Mg ha-¹, long GM, 0.07 Mg ha-¹) and oil (short GM, 0.12 Mg ha-¹). The results indicated (i) the N-gap in grain yield increases as the soybean cycle length decreases, (ii) the effect of limiting N on soybean growth and on protein and oil yield is greater when the cycle duration is shorter, however, when fertilized, protein concentration increases without reducing the oil concentration in genotypes with longer cycle duration.